Top 10 Lessons Learned from Electronic Medical Record Implementation in a Large Academic Medical Center - Rizer, Milisa K. (Perspect Health Inf Manag, 2015)
Electronic medical record (EMR) implementation efforts face many challenges, including individual and organizational barriers and concerns about loss of productivity during the process. These issues may be particularly complex in large and diverse settings with multiple specialties providing inpatient and outpatient care. This case report provides an example of a successful EMR implementation that emphasizes the importance of flexibility and adaptability on the part of the implementation team. It also presents the top 10 lessons learned from this EMR implementation in a large midwestern academic medical center. Included are five overarching lessons related to leadership, initial approach, training, support, and optimization as well as five lessons related to the EMR system itself that are particularly important elements of a successful implementation.